Tinjauan Hukum Penanggulangan Tindak Pidana Kepabeanan Di Wilayah Hukum Bea Dan Cukai Sulawesi-Selatan Selama Masa Pandemi Covid-19 (PETITUM, 2022)
This study examines the legal review of the handling of customs crime in the Customs and Excise jurisdiction of SouthSulawesi during the Covid-19 pandemic, analyzing efforts to overcome customs smuggling crimes that affect efforts to overcome customs smuggling during the Covid-19 Pandemic in the Sulawesi region. -South This research uses empirical research type,collect data relating to the prevention of criminal acts in the customs area of South-Sulawesi.as regulated in the provisions of Article 102 letterb of Law Number 17 of 2006 regarding law enforcement for criminal acts of smuggling with the modus operandi of document forgery because many business actors are not registered so that efforts to find the owner of the goods are very difficult to identify.